The Dead Sea scrolls: a biography - Collins, John J. (Lives of great religious books, 2012)
The Discovery of the Scrolls -- The Essenes -- The Site of Qumran -- The Scrolls and Christianity -- The Scrolls and Judaism -- The Scrolls and the Bible -- The Battle for the Scrolls -- Appendix. Personalities in the Discovery and Subsequent Controversies